Кинетический анализ полимеризации α-метилстирола под действием тетрахлорида титана; Научные труды SWORLD; Т. 3, № 4 - Ионова Е. И. Елена Ивановна; Ляпков А. А. Алексей Алексеевич; Бондалетов В. Г. Владимир Григорьевич; Пуленските И. Р. (2007, 2007)
Заглавие с экрана